Prevalence and Management of Back Pain in Adolescent Idiopathic Scoliosis Patients: A Retrospective Study. (2015) - Théroux, Jean; Le May, Sylvie; Fortin, Carole; Labelle, Hubert
Abstract : BACKGROUND: Back pain (BP) has often been associated with adolescent idiopathic scoliosis (AIS), which is a three-dimensional deviation of the vertebral column. In adolescents, chronic pain appears to be a predictor of health care utilization and has a negative impact on physical, psychological and family well-being. In this population, BP tends to be persistent and may be a predictor of BP in adulthood. OBJECTIVE: To document the prevalence and management of BP in AIS patients. METHODS: A retrospective chart review of AIS patients who were referred to Sainte-Justine University Teaching Hospital (Montreal, Quebec) from 2006 to 2011 was conducted. RESULTS: A total of 310 randomly selected charts were reviewed. Nearly one-half of the patients (47.3%) mentioned that they experienced BP, most commonly in the lumbar (19.7%) and thoracic regions (7.7%). The type of BP was documented in only 36% (n=112) of the charts. Pain intensity was specified in only 21% (n=65) of the charts. In approximately 80% (n=248) of the charts, no pain management treatment plan was documented. CONCLUSIONS: The prevalence of BP was moderately high among the present sample of adolescents with AIS. An improved system for documenting BP assessment, type, treatment plan and treatment effectiveness would improve pain management for these patients.